Comparison of the in vitro corrosion behavior of biodegradable pure Zn in SBF, 0.9% NaCl, and DMEM. Issue 10 (13th May 2021) - Zhu, Xinglong; Guo, Pushan; Yang, Lijing; Xu, Cheng; Geng, Fang; Shen, Jianwei; Lu, Ting; Sun, Wensheng; Song, Zhenlun
Abstract: Zn‐based alloys are considered to be the new biodegradable implant materials due to their suitable degradation rate and good biocompatibility. The biocorrosion behavior of pure Zn in 0.9% NaCl, simulated body fluid, and Dulbecco's modified Eagle's medium (DMEM) was investigated by electrochemical and immersion tests. These tests revealed that pure Zn has the lowest corrosion rate in DMEM and the highest in 0.9% NaCl. Aggressive Cl − has an important effect on the corrosion process. Buffering agents, amino acids, and glucose have a close connection with corrosion resistance. Among the three solutions, DMEM with a similar ion concentration and necessary nutriments is recommended as the more suitable choice for estimating biodegradable alloys' in vitro degradation. Abstract : The biocorrosion behavior of pure Zn in 0.9% NaCl, simulated body fluid, and Dulbecco's modified Eagle's medium (DMEM) was investigated by electrochemical and immersion tests. These tests revealed that pure Zn has the lowest corrosion rate in DMEM and the highest in 0.9% NaCl. Among the three solutions, DMEM with a similar ion concentration and necessary nutriments is recommended as the more suitable choice for estimating biodegradable alloys' in vitro degradation.